Does the cycad genotoxin MAM implicated in Guam ALS-PDC induce disease-relevant changes in mouse brain that includes olfaction? - Kisby, Glen (Landes Bioscience, 2011)
Western Pacific amyotrophic lateral sclerosis (ALS) and parkinsonism-dementia complex (PDC), a prototypical neurodegenerative disease (tauopathy) affecting distinct genetic groups with common exposure to neurotoxic chemicals in cycad seed, has many features of Parkinson's and Alzheimer's diseases (AD), including early olfactory dysfunction. Guam ALS-PDC incidence correlates with cycad flour content of cycasin and its aglycone methylazoxymethanol (MAM), which produces persistent DNA damage (O(6)-methylguanine) in the brains of mice lacking O(6)-methylguanine methyltransferase (Mgmt(-/-)). We described in Mgmt(-/-)mice up to 7 days post-MAM treatment that brain DNA damage was linked to brain gene expression changes found in human neurological disease, cancer, and skin and hair development. This addendum reports 6 months post-MAM treatment- related brain transcriptional changes as well as elevated mitogen activated protein kinases and increased caspase-3 activity, both of which are involved in tau aggregation and neurofibrillary tangle formation typical of ALS-PDC and AD, plus transcriptional changes in olfactory receptors. Does cycasin act as a "slow (geno)toxin" in ALS-PDC?